STRATEGY OF INCREASING THE SELF RELIANCE OF BESUKI NA-OOGST TOBACCO FARMERS IN ADAPTING TO THE CLIMATE CHANGE - hesti herminingsih (UPT Penerbitan Universitas Jember, 2017)
This study aims to determine 1) Self reliance of Besuki Na-Oogst tobacco farmers in adapting to climate change. 2) Strategy to increase the self reliance of Na-oogst tobacco farmers in adapting to climate change. The research area determination is conducted purposely in Tanjungrejo, Wuluhan, Jember on the basis of consideration. The research method is using descriptive and analytical. The sampling technique used is Purposive Sampling. The samples is obtained by calculating (20%) of each population of farmers applying Good Tobbaco Practice (GTP) of 80 people and who do not apply GTP of 110 people. Based on the calculation results, it is obtained a sample of 18 people applying GTP and 22 people who do not apply GTP. The method of data analysis used is descriptive analysis. Formulation of self reliance improvement strategy is using SWOT analysis (Strength, Weakness, Opportunity, Threat). The results shows that 1) Indicator of self-reliance of farmers which include: a) Obtaining 43% credit loans in banking. b) Participation level in agricultural extension; 22% Present; 55% rare and 18% absent. c) Identifying the phenomenon of climate change 100%. d) Adaptation measures already undertaken (80% improvement of irrigation techniques, 20% improvement in soil processing techniques, 60% planting time change and 80% pest prevention techniques). 2) Based on the results of SWOT analysis is obtained IFAS score of 2.80 and EFAS is 2.9 so by using the matrix model of Internal External Wheelen Hunger can be determined the position of the strategy in the growth zone with the concentration strategy through horizontal integration.